Enhancing cost efficiency and sustainability in the supply chain of modular construction: Designing a data-driven solution - Sousa, Eduardo Luís Mota (2023)
The construction industry has long been a pillar of economic development, contributing significantly to global GDP while simultaneously exerting considerable environmental impact. The increased urgency to mitigate greenhouse gas emissions and the growing demand for sustainable construction practices have prompted construction companies to reassess their operations and develop innovative strategies. Recognizing the need to improve the transportation logistics for modular construction projects, "dst group - Domingos Da Silva Teixeira, S.A.”, a prominent construction company, found the necessity to better anticipate transportation costs and reduce carbon emissions. In pursuit of this objective, “dst group” enlisted the expertise of "Rangel Logistics Solutions," an established logistics company, to address this multifaceted challenge. This dissertation explores the work undertaken at Rangel Logistics Solutions, emphasizing the process of conceptualization and development of an innovative IT solution driven by predictive models for cost and emissions.